STUDI KASUS PERAN PENDAMPINGAN ORANG TUA PADA PEMBELAJARAN DARING DI SEKOLAH DASAR NEGERI 44 REJANG LEBONG - Hermawan Hermawan; Lukman (Universitas Bengkulu, 2022)
The purpose of this study is to describe the role of parental assistance and the impact of the role of parental assistance on online learning at the elementary school of 44th Rejang Lebong. This type of research is descriptive qualitative with a case study approach. The subjects in this study were the parents of 44th Rejang Lebong state elementary school students. The instruments used in this study were observation sheets, interview sheets, and documentation. The data obtained were analyzed through the interactive model of Miles, Huberman, and Saldana, namely data collection, data condensation, data display, and data verifications. The results of this study are the role of parental assistance, 1. Parents as potential developers, 2. Parents as role models for children, 3. Parents as motivators for children to learn, 4. Parents as facilitators, 5. Parents as supervisors, 6 Parents as evaluators. The impact that arises from the role of mentoring on onnline learning. 1. In the context of learning, 2. In the family context, 3. In the context of parents’ work.